Straits Settlements Blue Book (imports/exports) 1906-1907 vol. 45-47 (Great Britain : Public Record Office, 1971)
Mengandungi'Straits Settlement return of imports and exports for the year 1906';'Recapitulatory and comparative statement of the value of imports into and exports from the Colony of the Straits Settlements for the years 1905 and 1906';'Blue Book for the year 1907'.